Individual and combined effects of the GSTM1, GSTT1, and GSTP1 polymorphisms on leukemia risk: An updated meta-analysis - Zhao, Yan; Wang, Di; Zhang, Cheng-Yu; Liu, Yan-Ju; Wang, Xiao-Hui; Shi, Meng-Ying; Wang, Wei; Shen, Xu-Liang; He, Xiao-Feng (Frontiers in Genetics, 2022)
Several meta-analyses analyzed the association of GSTM1 present/null, GSTT1 present/null, and GSTP1 IIe105Val polymorphisms with leukemia risk. However, results of these meta-analyses were conflicting. Moreover, they did not evaluate the combined effects of the above three gene polymorphisms. Furthermore, they did not appraise the credibility of the positive results. Finally, many new studies have been published. Therefore, an updated meta-analysis was conducted. The aim of this study is to further explore the relationship of the above three gene polymorphisms with leukemia risk. We use the crude odds ratios (ORs) and 95% confidence intervals (CIs) were applied to evaluate the association on the individual and combined effects of the above three genes. Moreover, the false-positive report probability (FPRP) and Bayesian false discovery probability (BFDP) were applied to verify the credibility of these statistically significant associations.Overall, the individual GSTM1, GSTT1, and GSTP1 IIe105Val polymorphisms added leukemia risk. Combined GSTM1 and GSTT1, GSTM1 and GSTP1, GSTT1 and GSTP1 polymorphisms, positive results were also observed. However, no significant association was observed between the combined effects of these three polymorphisms with leukemia risk in overall analysis. Moreover, when only selecting Hardy–Weinberg equilibrium (HWE) and medium and high-quality studies, we had come to similar results. However, when the FPRP and BFDP values were applied to evaluate the credibility of positive results, the significant association were only observed for the GSTT1 null genotype with leukemia risk in Asians (BFDP = 0.367, FPRP=0.009). This study strongly suggests a significant increase in risk of leukemia in Asians for the GSTT1 null genotype.